Pelatihan Penyusunan Modul Praktikum di SMAN 6 Ogan Komering Ulu - Sagita Charolina Sihombing; Parmin Lumbantoruan (Jurnal Mitrawarga, 2022)
This community service was carried out at SMA Negeri 6 Ogan Komering Ulu (OKU), South Sumatra. SMA Negeri 6 Ogan Komering Ulu (OKU) is one of the senior high schools in Ogan Komering Ulu Regency, South Sumatra Province that already has Superior accreditation and has fairly good facilities. The available facilities include a fairly good school building, a large school yard to carry out outdoor sports activities or national ceremonies, and a school laboratory. This service activity is motivated by the availability of laboratories at SMA Negeri 6 OKU, but practicum devices such as practicum modules are not sufficient. Therefore, it is necessary to hold a module preparation training activity for teachers and students of SMA Negeri 6 OKU. This activity aims to provide material on the meaning of a practicum module, the stages of compiling a practicum module, and the format/framework of a practicum module. The results of community service showed that most of the training participants, especially teacher participants, were able to receive the training materials well.